1955
DOI: 10.1017/s0022172400000991
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Bacteriological Aspects of Impetigo Contagiosa

Abstract: Summary1. The results of an investigation into the clinical, epidemiological and bacteriological features of impetigo contagiosa, with special reference to the type identification of staphylococci and streptococci, are reported and discussed.2. Of 106 impetigo cases studied, Staphylococcus aureus was isolated alone from 86 lesions (81 %), Streptococcus pyogenes alone from 6 (5·6 %), and a mixed growth of Staph. aureus and haemolytic streptococci in 14 instances (13·2 %).3. Of the 100 strains of Staph. aureus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

1958
1958
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 26 publications
2
10
1
Order By: Relevance
“…For some time it has been recognized that group A streptococci from skin lesions seldom have M-antigens that are detectable with the antisera used in routine typing (Parker et al 1955;Barrow, 1955;Dillon et al 1967). Top et al (1967) have shown that this is not because 'skin' streptococci lack M-antigens, but because they belong to previously unrecognized or supposedly rare M-types.…”
Section: Discussionmentioning
confidence: 99%
“…For some time it has been recognized that group A streptococci from skin lesions seldom have M-antigens that are detectable with the antisera used in routine typing (Parker et al 1955;Barrow, 1955;Dillon et al 1967). Top et al (1967) have shown that this is not because 'skin' streptococci lack M-antigens, but because they belong to previously unrecognized or supposedly rare M-types.…”
Section: Discussionmentioning
confidence: 99%
“…However, even this small difference noted between the two groups (7.4 per cent) was found to be statistically significant at the 1 per cent probability level. Other reports of low association are those of Barrow (1955) that there were individuals who were perineal carriers but not nasal carriers, and that the staphylococci were not in the perineum as contaminants from the neighboring anal orifice, but actually were capable of multiplying in that site. In addition, they found that strains from individuals who were both nasal and perineal carriers were identical.…”
Section: Association Between Lesion Andmentioning
confidence: 99%
“…2 The epidemiology of boils and abscesses in primary care is poorly understood. Suppurative skin infections such as sycosis barbae, 3 impetigo, 4 and furunculosis 5 are more common in patients who are colonised with Staphylococcus aureus and there is evidence that boils and abscesses are associated with social deprivation, overcrowding, the use of communal facilities, obesity, diabetes, and impaired immunity. [6][7][8][9] Patients consulting primary care with a boil or abscess will be treated either with antibiotics or with surgical incision and drainage, 10 but treatment options for those with recurrent boils is limited beyond addressing any underlying immune disorders and screening for diabetes.…”
Section: Introductionmentioning
confidence: 99%